2017
DOI: 10.3345/kjp.2017.60.8.266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hypertensive encephalopathy in pediatric patients

Abstract: PurposeThe aim of this study was to assess the clinical characteristics of hypertensive encephalopathy according to the underlying etiologies in children.MethodsWe retrospectively evaluated 33 pediatric patients who were diagnosed as having hypertensive encephalopathy in Chonbuk National University Children's Hospital. Among the patients, 18 were excluded because of incomplete data or because brain magnetic resonance imaging (MRI) was not performed. Finally, 17 patients were enrolled and divided into a renal-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…Hypertensive encephalopathy is a result of cerebral hyperperfusion or an exceeded upper limit of autoregulation by cerebral vessels, which results in cerebral edema and petechial hemorrhages (35). A previous study demonstrated that hypertensive encephalopathy was more common in pediatric patients with renal disorders (34). Similarly, in the present study, there were 41 subjects diagnosed with hypertensive encephalopathy, among which renal diseases accounted for 82.9% of cases.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Hypertensive encephalopathy is a result of cerebral hyperperfusion or an exceeded upper limit of autoregulation by cerebral vessels, which results in cerebral edema and petechial hemorrhages (35). A previous study demonstrated that hypertensive encephalopathy was more common in pediatric patients with renal disorders (34). Similarly, in the present study, there were 41 subjects diagnosed with hypertensive encephalopathy, among which renal diseases accounted for 82.9% of cases.…”
Section: Discussionsupporting
confidence: 67%
“…Hypertensive encephalopathy manifests as an acute brain dysfunction (disturbance of consciousness, severe headache, convulsions, and visual impairment) induced by an acute and severe increase in BP, which may be one of the earliest symptoms of hypertension in children (34). Hypertensive encephalopathy is a result of cerebral hyperperfusion or an exceeded upper limit of autoregulation by cerebral vessels, which results in cerebral edema and petechial hemorrhages (35).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive encephalopathy is most commonly encountered in young and middle-aged patients with uncontrolled hypertension. The mean systolic blood pressure reported in pediatric HE patients ranges from 175 mmHg in renal-origin hypertension to 137 mmHg in non-renal-hypertension ( 51 ). HE is a clinical condition caused by elevated blood pressure and which can, per definition, be reversed by blood pressure reduction.…”
Section: Discussionmentioning
confidence: 99%
“…It can be of renal or extrarenal origin. Ahn et al 4) evaluated 33 pediatric patients who were diagnosed as having hypertensive encephalopathy. It appeared that renal artery stenosis was the first responsible etiology of renal origin hypertension.…”
Section: Discussionmentioning
confidence: 99%